Applicability of Femtosecond Lasers in the Cross-section Sampling of Works of Art. (6th March 2017) - Spence, Stephanie; Harada, Takaaki; Margiolakis, Athanasios; Deckoff-Jones, Skylar; Shugar, Aaron N.; Hamm, James F.; Dani, Keshav M.; Dani, Anya R.
ABSTRACT: Issues in traditional cross-section sampling of paintings and other cultural artifacts with a scalpel, such as crumbling, delamination and paint compression, can deter conservators from sampling fragile paint layers. Often, such sampling carries the risk of causing further damage from a scalpel, which outweighs the benefits of scientific investigation. Here, we show that femtosecond lasers offer a viable alternative to obtaining cross-sections with minimal damage to the surrounding artwork. A Regenerative Ti:Sapphire amplifier system with a pulse duration of 70 femtoseconds, a few milliwatts of average power and a repetition rate of 1 kHz (1000 pulses/sec) was used for the study. Tests were performed on oil paintings ranging in age from the 19 th century to late 20 th century. Effective settings were determined to be 2 mW of power at a speed of 10mm/sec using an 800nm laser. Preliminary results suggest femtosecond lasers could be a viable alternative for obtaining paint cross-sections when traditional sampling methods cause unnecessary damage to fragile materials.